Metacarpophalangeal joint hyperextension in rhizartrosis: is surgical correction necessary? - Pogliacomi, Francesco; Oldani, Danila; Schiavi, Paolo; Pedrazzini, Alessio; Ferrari, Andrea; Leigheb, Massimiliano; Pedrini, Martina Francesca; Vaienti, Enrico; Ceccarelli, Francesco; Calderazzi, Filippo (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Rhizarthrosis represents 10% of all arthritic manifestations and its prevalence increases with age and in women. The hyperextension of the metacarpophalangeal joint (MCPj) is consequent to a progressive dorsoradial subluxation of the trapeziometacarpal joint (TMj) in advanced osteoarthritis. The aim of this retrospective study is to evaluate the clinical and functional results of 32 patients affected by advanced rhizarthrosis who underwent to modified Burton-Pellegrini’s trapeziectomy in absence of surgical correction of MCPj hyperextension in order to understand when this last step is really necessary. Methods: Patients were assessed trough DASH and PRWHE questionnaires; the functionality of the hand was assessed by carrying out specific test (grip strength, key-pinch, kapandji test, reduction of wrist flexion strength) and the degree of MCP joint hyperextension was recorded. Results: Clinical evaluation and individual satisfactory were positive in most cases (mean DASH 19 and mean PRWHE 21.8, with a reduction of 77% of VAS pain score). Kapandji test was excellent in 26 patients and grip strength and key pinch were stackable in operated and non-operated hands. Twenty-five out 32 patients presented a MCP joint hyperextension between 0° and 5°, 5 of 10° and other 2 of 15°. Conclusion: Modified Burton-Pellegrini’s trapeziectomy is a valid option to treat patient with TMj osteoarthritis. The absence of surgical correction of the MCPj does not affect clinical and functional results in deformities